1982
DOI: 10.1084/jem.155.2.432
|View full text |Cite
|
Sign up to set email alerts
|

Serial depletion and regeneration of the murine hematopoietic system. Implications for hematopoietic organization and the study of cellular aging

Abstract: The mouse hematopoietic system was subjected to repeated depletion and regeneration either by serial transfer of bone marrow cells through lethally irradiated recipients or by repeated treatment with the cycle-active drug hydroxyurea (HU). The capacity of surviving stem cells to proliferate and self-renew was assayed at intervals by two methods: (a) the spleen colony method; and (b) competitive repopulation of irradiated recipients using chromosome markers, with normal bone marrow cells as an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(45 citation statements)
references
References 33 publications
(52 reference statements)
4
41
0
Order By: Relevance
“…Both this population and that remaining after the selective killing of cells synthesizing DNA had an AI close to 1. This is consistent with the findings of Ross et al (8) showing that the proportion of cycling CFU-S does not necessarily reflect the proportion of the CFU-S subset with elevated proliferative capacity.…”
Section: Rapidly Proliferating Cfu-s Don't Represent a Primitive Cfu-supporting
confidence: 82%
See 1 more Smart Citation
“…Both this population and that remaining after the selective killing of cells synthesizing DNA had an AI close to 1. This is consistent with the findings of Ross et al (8) showing that the proportion of cycling CFU-S does not necessarily reflect the proportion of the CFU-S subset with elevated proliferative capacity.…”
Section: Rapidly Proliferating Cfu-s Don't Represent a Primitive Cfu-supporting
confidence: 82%
“…Recent studies have shown that the capacity of the stem cell compartment to restore hematopoiesis in irradiated mice is not compromised either during aging of the animal (21) or after 'aging' simulated by repetitive rounds of proliferation caused by repeated hydroxyurea injections (8). In fact, in both studies, old stem cells were more effective than young stem cells in restoring hematopoiesis.…”
Section: Rapidly Proliferating Cfu-s Don't Represent a Primitive Cfu-mentioning
confidence: 76%
“…3,40 Ectopic transplantation of individual fibroblastic clones grown in vitro from mouse marrow beneath the renal system to recover to a normal level. 28 In our study population, we could demonstrate CFU-GM, but not LTC-IC capsule of syngeneic hosts demonstrated that approximately 15% produced a marrow organ containing the full spectrum regeneration. The persistent derangement of the LTC-IC compartment associated with a normal CFU-GM incidence of stromal cell types of the hematopoietic microenvironment.…”
Section: Hematopoietic Progenitorsmentioning
confidence: 78%
“…The one, short-term HSC (ST-HSC), possesses limited self-renewal potential, pluripotency, and only short-term reconstitution capacity, while the other, long-term HSC (LT-HSC) has long-term selfrenewal and hematopoietic reconstitution capacity. 6 While HSCs have been found to persist throughout life in almost constant numbers, 7,8 and while 3 to 5 consecutive transplantations of HSCs into lethally irradiated hosts have suggested that they might undergo 80 to 200 divisions, [9][10][11][12][13] their in vitro capacity for selfrenewal appears limited to about 20 cell divisions. 14 Therefore, the self-renewal capacity of LT-HSCs appears to be strongly dependent on conditions, which can be provided by the host in vivo, but are insufficient with current in vitro culture conditions.…”
Section: Introductionmentioning
confidence: 99%